On the Chaotic Variability of Deep Convection in the Mediterranean Sea. Issue 5 (15th March 2018) - Waldman, Robin; Somot, Samuel; Herrmann, Marine; Sevault, Florence; Isachsen, Pål Erik
Abstract: Chaotic intrinsic variability is a fundamental driver of the oceanic variability. Its understanding is key to interpret observations, evaluate numerical models, and predict the future ocean and climate. Here we study intrinsic variability of deep convection in the northwestern Mediterranean Sea using an ensemble eddy‐resolving hindcast simulation over the period 1979–2013. We find that the variability of deep convection is mostly forced but also, to a considerable extent, intrinsic. The intrinsic variability can dominate the total convection variability locally and over a single winter. It also makes up a significant fraction of its interannual variability but has only modest impacts on the long‐term mean state. We find that the occurrence of deep convection is random 18% of years at the basin scale, and 29% locally at the LION observational site. Spatially, the intrinsic variability is highest far from the continental shelf. We relate this pattern to baroclinic instability theory that takes bottom stabilization into account. Key Points: The chronology of deep convection is largely random due to the Intrinsic Ocean Variability arising from a mesoscale‐eddying ocean The spatial patterns of intrinsic variability can be explained by the effect of bottom topography on baroclinic instability Our results support the paradigm change from deterministic to probabilistic oceanography